Pig‐to‐Monkey Islet Xenotransplantation Using Multi‐Transgenic Pigs. Issue 10 (12th September 2014) - Bottino, R.; Wijkstrom, M.; van der Windt, D. J.; Hara, H.; Ezzelarab, M.; Murase, N.; Bertera, S.; He, J.; Phelps, C.; Ayares, D.; Cooper, D. K. C.; Trucco, M.
<x xml:space="preserve">Abstract</x> The generation of pigs with genetic modifications has significantly advanced the field of xenotransplantation. New genetically engineered pigs were produced on an α1, 3‐galactosyltransferase gene‐knockout background with ubiquitous expression of human CD46, with islet beta cell‐specific expression of human tissue factor pathway inhibitor and/or human CD39 and/or porcine CTLA4‐lg. Isolated islets from pigs with 3, 4 or 5 genetic modifications were transplanted intraportally into streptozotocin‐diabetic, immunosuppressed cynomolgus monkeys (n = 5). Immunosuppression was based on anti‐CD154 mAb costimulation blockade. Monitoring included features of early islet destruction, glycemia, exogenous insulin requirement and histopathology of the islets at necropsy. Using these modified pig islets, there was evidence of reduced islet destruction in the first hours after transplantation, compared with two series of historical controls that received identical therapy but were transplanted with islets from pigs with either no or only one genetic modification. Despite encouraging effects on early islet loss, these multi‐transgenic islet grafts did not demonstrate consistency in regard to long‐term success, with only two of five demonstrating function beyond 5 months.